2011
DOI: 10.1158/0008-5472.can-11-0036
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Activated by Replication Stress–Induced Expression of Midkine Drives Epithelial–Mesenchymal Transition and Chemoresistance in Pancreatic Cancer

Abstract: The incidence of pancreatic ductal adenocarcinoma (PDAC) nearly equals its mortality rate, partly because most PDACs are intrinsically chemoresistant and thus largely untreatable. It was found recently that chemoresistant PDAC cells overexpress the Notch-2 receptor and have undergone epithelial-mesenchymal transition (EMT). In this study, we show that these two phenotypes are interrelated by expression of Midkine (MK), a heparin-binding growth factor that is widely overexpressed in chemoresistant PDAC. Gemcita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 35 publications
2
70
0
Order By: Relevance
“…Moreover, we have identified that gemcitabine dose-dependently induced expression and secretion of MK followed by activation of Notch signaling to promote epithelial-mesenchymal transition (EMT) and intrinsic as well as acquired chemotherapy resistance through upregulation of NF-kB. In addition, our results explained for the first time how MK may trigger cancer cells to become more resistant against cell death and how it promotes cell viability (9). Recently, we and others have shown that the secretion of MK in tumor cells may serve as biomarker for gastrointestinal tumors and glioblastomas (10,11).…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Moreover, we have identified that gemcitabine dose-dependently induced expression and secretion of MK followed by activation of Notch signaling to promote epithelial-mesenchymal transition (EMT) and intrinsic as well as acquired chemotherapy resistance through upregulation of NF-kB. In addition, our results explained for the first time how MK may trigger cancer cells to become more resistant against cell death and how it promotes cell viability (9). Recently, we and others have shown that the secretion of MK in tumor cells may serve as biomarker for gastrointestinal tumors and glioblastomas (10,11).…”
Section: Introductionmentioning
confidence: 67%
“…The list of MK interacting receptors on cell surface is still growing, since we were recently able to identify the Notch-2 receptor as a new MK interactor in PDAC cells whose activation by extracellular MK ended in a highly chemoresistant phenotype accompanied by EMT (9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations